Mediation Role of Organizational Culture on Transport Costing - Tapiwa Christopher Mujakachi; Marian Tukuta; Maria Tsvere (ExcelingTech, 2023)
The culture of an organization is influenced as the organization faces and learns how to cope with external and internal encounters. Those principles are maintained as the organization's way of doing business offers an effective adaptation to environmental problems and maintains success. The study sought to ascertain the importance of organizational culture in road freight transport sector in Zimbabwe. The road freight sector has been characterized by unprofessional behaviour and incompetent management. Organizational culture is key to defining the uniqueness of an organization, brand, philosophy, and how it relates to business ethics and all other stakeholders. Globally organizational culture has been given great eminence and priority as strategy followed culture in business performance. This was a quantitative study of road freight transport sector across Zimbabwe with a population of 1256 registered companies and a randomly picked sample size of 384 registered road freight companies out of 1256 companies from which data were collected. A total of 384 questionnaires were distributed and 291 were retrieved giving a response rate of 75.6%. Structured questionnaires were used to collect data. Reliability was checked using Cronbach’s alpha (?). Before conducting structural equation modelling, data were validated using exploratory factor analysis, convergent validity, and discriminant validity. SPSS® version 21 and AMOS® version 21 were used to analyse the data. The findings showed that organizational culture can help to mediate the relationship between transportation costs and firm competitiveness. The findings suggest that organizational culture has a significant impact on the relationship between transportation costs and firm competitiveness. The study also found out that all the registered companies that took part in the research confirmed that the value of time phenomenon was alien to their business organisational culture practices as they worked on assumptions. They also indicated loss of business due to customer complaints. The study recommends policy formulation for companies that emphasizes standard operating procedures and good time management as organisational culture for firms to be competitive.